Effects of Total Red Meat Consumption on Glycemic Control and Inflammation: A Systematically Searched Meta-analysis and Meta-regression of Randomized Controlled Trials (OR22-08-19) - O'Connor, Lauren (Curr Dev Nutr, 2019)
OBJECTIVES: Our objective was to assess effects of total red meat consumption on markers of glycemic control and inflammation using RCT data. Based on observational studies suggesting that higher red meat consumption increases type 2 diabetes risk, we hypothesized that higher red meat consumption would negatively influence markers of glycemic control and inflammation. METHODS: We identified 1171 articles via PubMed, Cochrane, and CINHAL up to August 2018. Inclusion criteria were 1) RCTs in which groups consumed ≥ vs <0.5 servings/d of total red meat i.e., a commonly recommended intake, 2) age ≥ 19 y, 3) not pregnant/lactating for females, 4) no diagnosed cardiometabolic disease, and 5) reported outcomes of fasting glucose, insulin, homeostatic model assessment for insulin-resistance (HOMA-IR), HbA1c, C-reactive protein (CRP), interleukin-6 (IL-6), or tumor necrosis factor-α (TNF-α). We used 1) repeated measures ANOVA to assess pre to post changes, 2) random-effects meta-analyses to assess relative differences between intervention and control, and 3) meta-regressions to assess effects of various factors on pre to post changes. We also performed these analyses within groups of studies defined by the following design characteristics: weight loss, macronutrient distribution, comparison protein source, eating pattern, body weight status, and red meat types. RESULTS: Glucose, insulin, and HOMA-IR decreased pre to post-intervention but HbA1c, CRP, IL-6, and TNF-α did not change over time for control and intervention. There was no differential effect of consuming ≥ vs <0.5 servings/d of red meat for any outcome (Table 1). Consuming ≥ vs <0.5 servings/d of red meat showed greater decreases in insulin when carbohydrates were replaced with red meat but lesser decreases in HOMA-IR when macronutrient distributions were matched between intervention and control eating patterns. Meta-regressions showed no dose-response relationship between red meat consumption and blood concentrations of any outcome variable (Table 2). CONCLUSIONS: Consuming above a commonly recommended intake of 0.5 servings of total red meat per day, or about three 3 oz. servings per week, does not negatively influence markers of glycemic control or inflammation in groups of adults without diagnosed cardiometabolic disease. FUNDING SOURCES: The Pork Checkoff. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: